2013
DOI: 10.3109/13880209.2013.768273
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative burst and hepatoprotective effects of ethanol root extract ofHippocratea africanaagainst paracetamol-induced liver injury

Abstract: Context: Hippocratea africana (Willd.) Loes. ex Engl. (Celastraceae) root is used traditionally as an antipoison or antidote to treat liver diseases. Objective: To evaluate antioxidative burst and hepatoprotective potentials of H. africana against paracetamol-induced liver injury in rats. Materials and method: Antioxidative burst activity of the extract (1-100 mg/ml) in whole blood, neutrophils and macrophages was investigated using a luminol/lucigenin-based chemiluminescence assay. The hepatoprotective effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…APAP can stimulate elevations in ROS levels causing cellular oxidative stress, which results in hepatotoxicity and nephrotoxicity ( 16 , 63 ). Therefore, several antioxidant drugs that prevent APAP-induced cellular damage have been investigated ( 64 – 68 ). Vitamin C, an antioxidant, was used to inhibit the cytotoxic effects of APAP in the hMSCs in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…APAP can stimulate elevations in ROS levels causing cellular oxidative stress, which results in hepatotoxicity and nephrotoxicity ( 16 , 63 ). Therefore, several antioxidant drugs that prevent APAP-induced cellular damage have been investigated ( 64 – 68 ). Vitamin C, an antioxidant, was used to inhibit the cytotoxic effects of APAP in the hMSCs in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The ethanol extract of H. Africana roots was shown to exhibit good anti-inflammatory, analgesic and anti-pyretic properties (Okokon et al, 2008), antioxidative burst and hepatoprotective effects (Okokon et al, 2013). Other species of Hippocratea which possess anti-inflammatory activity are H. excels Kunth (Perez et al, 1995) and H. indica Willd.…”
Section: Introductionmentioning
confidence: 99%
“…(Ogbole et al, 2007). Few previous chemical studies are reported in the literature about H. africana, concerning fatty acid content J o u r n a l P r e -p r o o f (Ita and Ngochindo, 2014) and volatile components of roots (Okokon et al, 2013). In previous studies on Hippocratea genus, isolated compounds from H. excels include lupeol acetate, hippocrateine I-III, mayteine, pentacyclic tritepenoids, ÎČ-sitosterol, epicatechin, friedelin, canophyllal, sesquiterpene evinonate alkaloids, as well as benzyl isothiocyanates (Calzada and Mata, 1995;Navarrete et al, 2002;Mena-Rejon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) (22) and alkaline phosphatase (ALP) (23) of the liver enzymes were chemically determined using specific kits. Serum total protein (TP) was chemically determined (24). Serum albumin (Alb) and globulins (Glb) were determined according to the method of Fernandez et al (25).…”
Section: Biochemical Analysismentioning
confidence: 99%